Kinetics of the drying process of cultivated mushrooms - Burlaka, Tatiana; Dubkovetskyy, Igor; Malezhik, Ivan (My University, 2016)
In investigation of the drying process of cultivated mushrooms by known methods, it was established that none of the methods of drying can provide the minimum electric energy consumption for the preparation of the final product with high quality indices. That is why we proposed to combine two methods, namely, to use infrared rays in combination with convection under forced air circulation.
Keywords: культивовані гриби; кінетика сушіння; інфрачервоне випромінювання; конвекція; культивируемые грибы; кинетика сушки; инфракрасное излучение; конвекция; cultivated mushrooms; kinetics of drying; infrared radiation; convection; кафедра процесів і апаратів харчових виробництв